'How families live …' – the views and experiences of parent-carers who provide family placements to intellectual disability nursing students. (December 2017) - McClimens, Alex; Finlayson, Janet; Darbyshire, Chris
Aim: We aimed to learn about the value of family placements from the perspective of parent-carers who provide them to nurse students via a Scottish university Family Placement Scheme. Method: Qualitative interviews were conducted with seven parent-carers who provided a family placement over two academic years. Descriptive data was analysed, organized into themes and subject to content analysis: parents' descriptions of caring; their perceived value of family placements; and their views and experiences of participation in intellectual disability nurse education. Results: Family placements are beneficial to nurse students and families with children with an intellectual disability. Description of wider aspects of caring was provided, offering insight into learning experiences of students on placement. Conclusion: This model of learning provides opportunities for students to appreciate the reality of caring for a relative with an intellectual disability at home. Students develop their practice skills for working in partnership with family carers.